THE ANATOMY OF SPEED - Parisi, Bill (Human Kinetics, 2022)
The Anatomy of Speed provides a detailed anatomical breakdown of various components of athletic speed, agility, and change of direction. It also includes expert training tips to improve performance, as well as examples of and guidelines for effective speed training program design.